The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations THE HEAD LOUSE A small-tooth comb should be used to free the head of lice, but it is even more important to get rid of the nits (the eggs of head lice which are glued on to the hairs). The following methods may be used for this: (i) If there are many nits the hair should be cut quite short, and any nits remaining on the short hairs removed. (ii) If there are not many nits present, the hairs with nits on them should be cut away or the nits pulled from the hairs after thoroughly lathering and washing with soft soap and water. (iii) Nits can also be removed by using a steel nit comb. To remove nits with this comb as speedily as possible, a strand of hair should be taken, greased with olive oil and water, and the comb passed through the hair and pulled along the length of the hair away from the head. [illustration] For ridding the hair of nits. RATS AND MICE If the larder is rat-and-mouse proof, and if no food is ever left about, and the lid is kept firmly on the dustbin, it is unlikely that rats or mice will become a problem. Mouse traps, baited with bacon or toasted cheese, can be set at night and mouse-holes should be securely stopped. If there is evidence that a rat has found a way into the house, inform the Estate Manager or Sanitary Inspector at once. A cat, if you are allowed to keep one, is an excellent rat and mouse preventive. Rats and mice can do a great deal of damage. It is the tenant's duty to eradicate them. [illustration] Bait this with cheese! [illustration] 22 177/5/8/2